Perbandingan Metode MFEP dan SAW Dalam Menentukan Wisata Kuliner Terbaik Di Kota Medan - Rahelya br Marpaung (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
Culinary Tourism is one of the prides of the city of Medan because it has a wide variety of culinary available. Culinary tourism is now one of the activities that must be done by tourists when visiting a Medan city. However, the lack of information about culinary tourism destinations to be visited, especially in the city of Medan, is one of the problems for tourists in determining the criteria for culinary tourism that is suitable for tourists such as spots, food, facilities, rides and distances. In solving these problems we need a system that can provide information about culinary tourism destinations. Decision support system is one system that can be implemented into these problems. With a decision support system, it can assist tourists in determining the culinary tourism destinations to be visited based on the required criteria. The decision system uses the MFEP and SAW methods as well as the application of the application using Visual Basic Net 2010 software using a sql server database. By using the desktop-based application of Visual Basic Net 2010 and a decision system using the MFEP and SAW methods, the author will develop a system that can assist tourists in determining culinary tourism destinations based on the wishes of tourists with various predetermined aspects.